Gesetzesgerechtigkeit und Glaubensgerechtigkeit in Rom 4:13—25: In Gesprach mit E P Sanders - Toit, Andries Bernardus du (Hervormde teologiese studies, 1988)
Righteousness through the law and rightousness through faith in Rm 4:13—25: A reaction to EP Sanders In his book Paul and Palestinian Judaism EP Sanders has presented us with a most stimulating approach. His main thesis that traditional New Testament research has misunderstood Paul as well as first century Palestinian Judaism, received positive comment from many quarters. According to Sanders first century Judaism should be understood within a context of gratuity rather than as a religion of works. A survey of Rm 4:13-25 shows, however, that at least Paul viewed righteousness through the law as an entrance requirement in Judaism. As far as the Jewish sources are concerned a preliminary investigation indicates that Sanders' usage and interpretation of these sources are questionable. It seems highly probable that Sanders has misinterpreted Palestinian Judaism and for that reason also Paul's criticism of it.